Modeling Geomagnetic Interference on Railway Signaling Track Circuits. Issue 1 (6th January 2021) - Boteler, D. H.
Abstract: Misoperation of railway signaling during geomagnetic disturbances has occurred in a number of countries. Railway signals are activated by track circuits that detect the presence of a train in a particular rail section, but geomagnetically induced electric fields can interfere with the track circuit operation, causing the wrong signal to be displayed. This paper develops a new model for track circuit operation that includes the induced geoelectric fields produced by geomagnetic field variations. Rails are modeled as transmission lines with series impedance given by the rail resistance and parallel admittance determined by the current leakage from the rail through the ballast to ground. The transmission line model is then converted into an equivalent‐pi circuit for each rail and these are combined with the track circuit power and relay components to form a nodal admittance network for the track circuit. This is used to examine the effect of induced geoelectric fields on track circuit operation. First, an individual track circuit is examined and it is shown how the length, between insulating rail joints, of the individual rails influences the geomagnetic interference voltage produced across the track circuit relay. Then a series of track circuits is considered: A general solution is developed and then the conditions are identified that allow this to be reduced to a simpler solution considering each track circuit individually. This modeling provides insight into the conditions that produce signaling problems and provides the tools to assess the geomagnetic hazard to railway signaling. Key Points: Geomagnetic interference in railways using track circuits to control signals can be modeled using a nodal admittance network approach Non‐electrified railways with "balanced" track circuits experience common mode interference that does not affect track circuit operation Electrified railways with "asymmetrical" track circuits experience differential mode interference that can affect track circuit operation